Effects of Maturity Stages on the Nutritive Composition and Silage Quality of Whole Crop Wheat - Xie, Z. L. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
The changes in yields and nutritive composition of whole crop wheat (Triticum aestivum L.) during maturation and effects of maturity stage and lactic acid bacteria (LAB) inoculants on the fermentation quality and aerobic stability were investigated under laboratory conditions. Whole crop wheat harvested at three maturation stages: flowering stage, milk stage and dough stage. Two strains of LAB (Lactobacillus plantarum: LAB1, Lactobacillus parafarraqinis: LAB2) were inoculated for wheat ensiling at 1.0×10(5) colony forming units per gram of fresh forage. The results indicated that wheat had higher dry matter yields at the milk and dough stages. The highest water-soluble carbohydrates content, crude protein yields and relative feed value of wheat were obtained at the milk stage, while contents of crude fiber, neutral detergent fiber and acid detergent fiber were the lowest, compared to the flowering and dough stages. Lactic acid contents of wheat silage significantly decreased with maturity. Inoculating homofermentative LAB1 markedly reduced pH values and ammonia-nitrogen (NH(3)-N) content (p<0.05) of silages at three maturity stages compared with their corresponding controls. Inoculating heterofermentative LAB2 did not significantly influence pH values, whereas it notably lowered lactic acid and NH(3)-N content (p<0.05) and effectively improved the aerobic stability of silages. In conclusion, considering both yields and nutritive value, whole crop wheat as forage should be harvested at the milk stage. Inoculating LAB1 improved the fermentation quality, while inoculating LAB2 enhanced the aerobic stability of wheat silages at different maturity stages.